Pengembangan Perumahan Berbasis Pemberdayaan Masyarakat Desa Wisata Serangan Terintegrasi Di Kota Denpasar - gede, cipta sudewa atmaja (Jurnal Alam Lestari, 2025)
The phenomenon that occurs in Serangan Tourism Village from the perspective of housing and residential areas is the continued discovery of Uninhabitable Houses based on the 2014 Denpasar City e-Uninhabitable Houses data of 5 units out of a total of 12 RTLHs that have existed since 2017. This fact is not commensurate with the existence of Serangan Tourism Village as the Kura Kura Bali Special Economic Zone (Government Regulation Number 23 of 2023). The problems found are the absence of a housing development policy in Serangan Tourism Village based on community empowerment, the fading of housing models with characteristics typical of Serangan Tourism Village, and the uneven ability of Human Resources in the IT field of public services for the provision of habitable houses. Mayoral Regulation Number 60 of 2014 concerning Habitable Houses by including the novelty of other legitimate budget sources in the improvement of LH Habitable Houses, creating the Paruman Dewi Sita Masterplan Pre-Design, conducting digital publications as a public sector marketing strategy and sharpening the achievement of the Vision and Mission of the Denpasar City Government in Serangan Tourism Village. The changes produced and the benefits obtained by the community in Serangan Tourism Village are visible. Paruman Dewi Sita is a breakthrough solution for arranging the provision of livable houses in order to support the face of Serangan Tourism Village in an integrated manner with other infrastructure. Paruman Dewi Sita is designed to be a solution for a housing development model in Serangan Tourism Village based on community empowerment and optimizing local wisdom as a housing development that has adapted to the progress of the times. Recommendations for the sustainability of the Paruman Dewi Sita program.